ASUHAN KEPERAWATAN ANAK An. C DENGAN GANGGUAN SISTEM PENCERNAAN PENYAKIT DEMAM TIFOID DIRUMAH SAKIT TENTARA TK IV.01.07.01 PEMATANGSIANTAR - Kiki Amelia; Abdul Basit Lubis (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Typhoid fever is an acute infectious disease caused by Salmonella typhi that affects the digestive system. The World Health Organization (WHO) estimates that approximately 9 million cases and 110,000 deaths occur worldwide each year. This study aimed to implement nursing care for a pediatric patient (An. C) diagnosed with typhoid fever. Methods: This study employed a descriptive method using a case study approach involving one pediatric patient who was hospitalized for three days (April 16–18, 2026) at Army Hospital TK IV.01.07.01 Pematangsiantar. Data were collected through interviews, observation, physical examination, and documentation. Results: The nursing care outcomes demonstrated an improvement in the patient's condition after 3 × 24 hours of nursing interventions. The patient's body temperature decreased from 39.3°C to 37.4°C, appetite and nutritional intake improved, and sleep quality became better. Nursing problems, including hyperthermia, imbalanced nutrition: less than body requirements (nutritional deficit), and disturbed sleep pattern, showed improvement according to the expected outcomes and were categorized as partially resolved. Conclusion: Comprehensive nursing care for children with typhoid fever can improve the patient's condition by managing hyperthermia, enhancing nutritional status, and improving sleep patterns. Recommendations: Nurses are expected to monitor the patient's body temperature regularly, maintain adequate nutritional intake, and provide appropriate interventions to improve the patient's sleep quality.